2018
DOI: 10.1038/s41375-018-0167-0
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of the selective small-molecule UBA1 inhibitor, TAK-243, in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is an aggressive hematologic malignancy for which new therapeutic approaches are required. One such potential therapeutic strategy is to target the ubiquitin-like modifier-activating enzyme 1 (UBA1), the initiating enzyme in the ubiquitylation cascade in which proteins are tagged with ubiquitin moieties to regulate their degradation or function. Here, we evaluated TAK-243, a first-in-class UBA1 inhibitor, in preclinical models of AML. In AML cell lines and primary AML samples, TAK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 46 publications
9
79
0
Order By: Relevance
“…The evolution of parasite resistance to such inhibitors is also an important concern that should be address early in the drug discovery process [ 26 ]. A previous study showed that upon MLN7243 treatment HsUBA1 Ala580, which has been designated as the gatekeeper residue, is replaced with a serine [ 55 ], thereby providing drug resistance. PfUBA1 has an alanine at this position (Ala633) and hence drug resistance to adenosyl sulfamates might develop in P .…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of parasite resistance to such inhibitors is also an important concern that should be address early in the drug discovery process [ 26 ]. A previous study showed that upon MLN7243 treatment HsUBA1 Ala580, which has been designated as the gatekeeper residue, is replaced with a serine [ 55 ], thereby providing drug resistance. PfUBA1 has an alanine at this position (Ala633) and hence drug resistance to adenosyl sulfamates might develop in P .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we evaluated a first-in-class small-molecule UBA1 inhibitor developed by Takeda Pharmaceuticals, TAK-243, in preclinical models of AML [4]. TAK-243 is an adenosine sulphamate related to pevonedistat, a NEDD8-activating enzyme (NAE) inhibitor and the prototype of this class of mechanism-based E1 inhibitors [5].…”
mentioning
confidence: 99%
“…As such, targeting the enzymes responsible for either the addition or removal of ubiquitin offers a potential therapeutic avenue. Encouragingly, a number of small molecule inhibitors of ubiquitin-associated enzymes are currently entering pre-clinical trials (51)(52)(53)(54)(55). Here, we screened the TCGA cervical cancer database for the expression of DUBs, enzymes which catalyse the remove of ubiquitin from protein substrates (5).…”
Section: Discussionmentioning
confidence: 99%